2015
DOI: 10.1107/s1399004715017216
|View full text |Cite
|
Sign up to set email alerts
|

Structure and inhibition of subunit I of the anthranilate synthase complex of Mycobacterium tuberculosis and expression of the active complex

Abstract: The tryptophan-biosynthesis pathway is essential for Mycobacterium tuberculosis (Mtb) to cause disease, but not all of the enzymes that catalyse this pathway in this organism have been identified. The structure and function of the enzyme complex that catalyses the first committed step in the pathway, the anthranilate synthase (AS) complex, have been analysed. It is shown that the open reading frames Rv1609 (trpE) and Rv0013 (trpG) encode the chorismate-utilizing (AS-I) and glutamine amidotransferase (AS-II) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Other bacterial AS such as the fused Streptomyces venezuelae are not only monomeric, but also cannot use ammonia instead of glutamine to aminate chorismate (Ashenafi et al, 2015 ). Among pathogenic bacteria from which crystallographic structures of AS are available, the oligomeric organization differs substantially between Serratia marcrescens and S. typhimurium , where the α 2 β 2 tetramer associates via the AS-I subunits (Spraggon et al, 2001 ; Figure 3Bi ), while in the M. tuberculosis enzyme, AS-I is a homodimer, even when AS-II is present (Bashiri et al, 2015 ; Figure 3Bii ). In the last enzyme, the allosteric binding site for the inhibitor tryptophan is found near the interfacial region.…”
Section: The Biosynthesis Of Aaamentioning
confidence: 99%
“…Other bacterial AS such as the fused Streptomyces venezuelae are not only monomeric, but also cannot use ammonia instead of glutamine to aminate chorismate (Ashenafi et al, 2015 ). Among pathogenic bacteria from which crystallographic structures of AS are available, the oligomeric organization differs substantially between Serratia marcrescens and S. typhimurium , where the α 2 β 2 tetramer associates via the AS-I subunits (Spraggon et al, 2001 ; Figure 3Bi ), while in the M. tuberculosis enzyme, AS-I is a homodimer, even when AS-II is present (Bashiri et al, 2015 ; Figure 3Bii ). In the last enzyme, the allosteric binding site for the inhibitor tryptophan is found near the interfacial region.…”
Section: The Biosynthesis Of Aaamentioning
confidence: 99%
“…Tryptophan biosynthesis is an essential pathway in mycobacteria in vitro as well as in vivo (Zhang et al, 2013;Wellington et al, 2017). The pathway is regulated via a negative feedback loop in which the end product tryptophan acts as allosteric inhibitor of the first committed enzymatic step of the pathway catalyzed by anthranilate synthase TrpE (Bashiri et al, 2015). Thus, we hypothesized that IPA may mimic tryptophan as allosteric inhibitor and block tryptophan synthesis.…”
Section: Ipa Blocks Mycobacterial Tryptophan Biosynthesis By Mimickinmentioning
confidence: 99%
“…Zhang et al (12) and Wellington et al (13) have demonstrated that the Trp biosynthetic pathway is essential for growth and viability of M. tuberculosis in standard (Trp-free) medium as well as in macrophages and mice. In M. tuberculosis , Trp regulates its own synthesis by acting as a cooperative allosteric inhibitor of anthranilate synthase TrpE, which catalyzes the first committing step in the pathway (14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…The homodimeric M. tuberculosis protein TrpE (Rv1609), in conjunction with glutamine amidotransferase (TrpG) providing ammonia, catalyzes the formation of anthranilate from chorismate (15, 16). The N-terminal region of TrpE contains the allosteric Trp binding motif 53 LLESX 10 S 67 (15). The 10-amino-acid residue X 10 loops of the two TrpE subunits approach each other at the interface, providing part of the structural framework for the cooperative allosteric inhibitory effect of Trp binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation